A Systemic Approach to Inceptive Constructions in Lithuanian - Rolandas Mikulskas (Lietuvių Kalba)
The article deals with inceptive constructions in Lithuanian in a systemic way. In the article a thorough overview of eighteen Lithuanian verbs taking infinitives as their complements is given. They are (given in the preterital form): pradėjo, ėmė (‘started’; ‘began’); puolė, šoko, metėsi (orig. ‘rushed at, to’; ‘jum- ped forward’); suskato, suskubo, sukruto, subruzdo, sujudo (orig. ‘stirred’; ‘moved’; ‘bustled up’); prapliupo, pratrūko (orig. ‘burst’; ‘broke open’; ‘gushed’; ‘spouted’), pasiuto and (synonymous with it) pašėlo (orig. ‘went mad’; ‘got furious’); leidosi, pasileido (orig. ‘let, allowed, permitted oneself’); griebėsi (/ griebė), kibo (orig. ‘grasp’; ‘get hold of’). When used in a construction with the infinitive, these verbs serve the grammatical function of inceptive markers designating the beginning (or start) of an infinitival event. They thus belong to the family of so-called phasal verbs, and the constructions they underlie are phasal constructions. They are, however, scarcely recognized as such (maybe except for the pradėjo and ėmė constructions with infinitive) in traditional Lithuanian lexicography. A construction grammar approach to the phenomenon of the phasal complementation allows us to treat the inceptive constructions under discussion uniformly, as members of the same grammatical category, and the verbs mentioned above, when serving as inceptive markers of the infinitival event, can reasonably go under separate senses in dictionary entries, especially in the cases when the inceptive constructions these verbs underlie are well entrenched in language usage.